Financial evaluation of the potato production system (Solanum tuberosum L.) in Oicata, Boyaca - Avendaño-Gómez, Elmer; González-Santos, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Financial feasibility is essential for decision making in a production system. Therefore all agricultural activity should use this tool to gain a greater understanding of its finantial exercise and also have an objective support to determine among other things whether to continue with the activity, diversify, combine it or lease the physical space where it is performed. The aim of this work is to conduct a financial evaluation in the production system of potato Solanum tuberosum variety Diacol capiro, in a participatory manner and with the inclusion of historical indicators, depending on time horizons and rate chance.The study population corresponded to 32 potato farmers enrolled in the company providing agricultural technical services (Epsagro) Oicata Township, Boyaca, 2014, of which 3 producers (large, medium and small) were selected for the research. The results indicate that the participatory rural diagnosis was a proper research tool for information, also there were differences in the structure of production cost in the different farmers. Besides in the municipality of Oicata was found that there are flaws in relevant operational and accounting standards, that should be corrected.